Cultural stereotypes in care contexts - Fernández-Ballesteros R (Dove Medical Press, 2018)
Rocío Fernández-Ballesteros,1 Macarena Sánchez-Izquierdo,2 Ricardo Olmos,3 Carmen Huici,4 Marta Santacreu,5 Rocío Schettini,6 María Ángeles Molina6 1Department of Psychobiology and Health, Autonomous University of Madrid, Madrid, Spain; 2Department of Psychology, Universidad Pontificia Comillas, Madrid, Spain; 3Department of Methodology, Autonomous University of Madrid, Madrid, Spain; 4Department of Social and Organizations Psychology, Universidad Nacional de Educación a Distancia, Madrid, Spain; 5Department of Psychology, Universidad Europea, Madrid, Spain; 6Department of Psychology, Universidad Francisco de Vitoria, Madrid, Spain Introduction: The main goal of the present study was to examine the stereotype content model (SCM) assumption for universality and to test whether the mediating role of cultural views about older adult caregivers is maintained in other health care contexts. Methods: One hundred and sixty professionals and volunteers who worked with older adults in day care centers (DCCs) and senior citizen centers (SCCs) and 1,151 participants from a representative sample of the Spanish population were examined using the SCM questionnaire; older adult and personnel functioning were assessed through an observation procedure with two subscales of the Evaluation Scale from the Sistema de Evaluación de Residencias de Ancianos. Results: The results showed that the context does not seem to influence the cultural views about older adults held by caregivers. All results support the cultural stereotype pattern in which members of the older adult group are viewed with high warmth (HW) and low competence (LC) as posited by the SCM model. With respect to the mediation of cultural stereotypes on caregivers/older adult functioning, this has not been supported in this study. Neither cultural views of warmth (predicted by the SCM) nor views of competence (from our previous studies) influence either caregiver functional behaviors or older adult functioning. Conclusion: Two post hoc hypotheses can be inferred: 1) there is more variability in competence and warmth in DCCs and SCCs and 2) although we did not find significant differences in the pattern of competence and warmth in perceived cultural stereotypes about older adults, more healthy environments could reduce the influence of cognitive views on behavior. Keywords: caregiving, prejudice, cultural stereotypes, caregiver functioning, older adult functioning